A new measure of decompression sickness in the rat - Buzzacott, Peter; Mazur, A.; Wang, Q.; Lambrechts, K.; Theron, M.; Mansourati, J.; Guerrero, F. (Hindawi Publishing Corporation, 2014)
In this study we assessed the reliability of a tilting-board grip score as a measure of decompression sickness in rats. In experiments using a hyperbaric compression/decompression protocol, rats were observed for signs of decompression sickness and their grip strength measured on a tilting particle board hinged to a metal frame. Angles at which rats lost grip were converted to gravitational vectors. Decreased mean grip scores following decompression were fitted to a logistic regression model with strain, age, and weight. Decrease in grip score was significantly associated with observed decompression sickness (P=0.0036). The log odds ratio for decompression sickness = 1.40 (decrease in grip score). In rats with no decrease in mean grip score there was a 50% probability of decompression sickness (pDCS). This increased steadily with decreases in mean grip score. A decrease of 0.3 had a 60% pDCS, a decrease of 0.6 had a 70% pDCS, and a decrease of 2.1 had a 95% pDCS. The tilting board grip score is a reliable measure of the probability of decompression sickness. © 2014 Peter Buzzacott et al.